PELATIHAN GAME EDUKASI BERBASIS SDGs DALAM UPAYA MEMBENTUK KARAKTER MELALUI PENGUATAN PROJEK PROFIL PELAJAR PANCASILA BAGI GURU MI ZIYADATUL ULUM DESA KAMBINGAN BARAT - Muhammad Misbahudholam AR; Framz Hardiansyah; Kurratul Aini; Ali Armadi; Choli Astutik (LPPM Universitas Bina Bangsa, 2023)
The purpose of this activity is to carry out community service at MI Ziyadatul Ulum, West Kambingan Village, which is one of the villages included in the Lenteng District of Sumenep Regency. Some of the findings in the school are: a) there are still few teaching aids or learning media in teaching and learning activities and b) teaching and learning activities are still applied conventionally. Therefore, researchers chose the program and offered training as a new science to add insight and provide new understanding to educators about learning media in the training process on the use of SDGs-based educatin games. The service carried out consists of training, especially for educators at MI Ziyadatul Ulum. The stages of this training are: the initial stage, by preparing for the training, the core of the training is the implementation, and the completion of the training implementation. The results of the activities are; a) training carried out for the community in West Kambingan Village on SDGs-based educational games in an effort to form a character for strengthening the pancasila student profile project has been carried out with good results; b) training activities in West Kambingan Village carried out at MI Ziyadatul Ulum received enthusiasm and a very satisfactory response from the teachers; and c) the community, especially teachers who participated in the training, understand the material well about how to use learning media packaged in the form of SDGs educational games using the Icando, Quizizz and Kahoot applications in making learning media through educational games while still instilling a character education in accordance with the strengthening of the pancasila student profile project.